The Internet as Utopia: Reality, Virtuality, and Politics - Cowles, Joshua (My University, 2009)
Literary utopias have the important function of social critique. They point out flaws in society by way of implicit comparison to an imaginary ideal place and society and help to create a desire for change. Like most technologies, the mainstream adoption of the Internet was surrounded by utopian rhetoric. But the Internet is more than just technology; it offers a virtual reality that is designed to simulate place, and this makes the Internet a utopia in itself rather than merely the subject of utopian thought. Simultaneously, the Internet is a firm part of traditional (non-virtual) reality, subject at least in part to the control of business interests and territorial governments. This weakens the social critique of the Internet. I argue that because of its unique character as a virtual reality, the Internet possesses a powerful transformative potential that inspires public and private attempts to control it. This tension is inherent in the relationship between reality and virtuality and manifests in legal clashes over issues of intellectual property and free speech.
Keywords: Utopias; Political Participation - Technological innovations; Information technology - Political aspects; Information society; Computers and civilization; Internet - Social aspects